2022
DOI: 10.1186/s12877-022-03214-0
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of a multicomponent exercise program and cognitive stimulation (VIVIFRAIL-COGN) on falls in frail community older persons with high risk of falls: study protocol for a randomized multicenter control trial

Abstract: Background Falls represent important drivers of intrinsic capacity losses, functional limitations and reduced quality of life in the growing older adult’s population, especially among those presenting with frailty. Despite exercise- and cognitive training-based interventions have shown effectiveness for reducing fall rates, evidence around their putative cumulative effects on falls and fall-related complications (such as fractures, reduced quality of life and functional limitations) in frail in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…This moderating effect emphasizes the necessity for tailored interventions that not only address frailty but also encompass fall prevention strategies for this vulnerable population. For those with a history of falls in the older adults with SCD, intervention programs could be designed to include multifaceted exercise plans ( 44 ). Such plans could serve the dual purpose of increasing PA levels in older adults with SCD while simultaneously reducing the risk of future falls.…”
Section: Discussionmentioning
confidence: 99%
“…This moderating effect emphasizes the necessity for tailored interventions that not only address frailty but also encompass fall prevention strategies for this vulnerable population. For those with a history of falls in the older adults with SCD, intervention programs could be designed to include multifaceted exercise plans ( 44 ). Such plans could serve the dual purpose of increasing PA levels in older adults with SCD while simultaneously reducing the risk of future falls.…”
Section: Discussionmentioning
confidence: 99%
“…Multicomponent exercise programmes and cognitive stimulation (which target potentially modifiable risk factors of this study) may reduce falls in frail community-dwelling older persons at high risk of falls [ 41 ]. Yet a recent systematic review found few studies investigating exercises interventions for people with mild cognitive impairment and concluded that there was insufficient evidence to inform clinical practice [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…After publication of this article [1], the authors reported that the statement in the Funding information section was incorrectly given as 'The present study is funded by a grant from the Spanish Ministry of Science and Innovation and the Instituto de Salud Carlos III (PI20/01546). ' and should have read 'The present study is funded by a grant from the Spanish Ministry of Science and Innovation and the Instituto de Salud Carlos III (PI20/01546), co-financed by FEDER funding' .…”
Section: Open Accessmentioning
confidence: 99%